GE_GERICHTE P/5363/2020 vom 7. Februar 2022 - GE Cour de justice (2022)
IN DUBIO PRO REO;AVEU;LÉSION CORPORELLE GRAVE;LÉSION CORPORELLE SIMPLE;TENTATIVE(DROIT PÉNAL);FIXATION DE LA PEINE;EXPULSION(DROIT PÉNAL) | CP.122; CP.22; CP.286; CP.121; CP.66a.al1